Stigmatization and social isolation experienced by Human Papillomavirus-positive women: A phenomenological study - Sanli, Cengiz; Dogan Yuksekol, Ozlem; Ulucan, Mihriban; Baltaci, Nazli (Routledge Journals, Taylor & Francis Ltd, 2025)
HPV is a common sexually transmitted infection strongly associated with cervical cancer. Beyond its physical health implications, an HPV-positive diagnosis often leads to stigma, shame, and social isolation, which remain insufficiently explored in the literature. This study was conducted to determine the levels of stigma and social isolation in HPV positive women. This qualitative study was conducted using a phenomenological research design. A total of 22 women participated in the study. Data were collected through face-to-face interviews conducted in Turkiye. Snowball sampling was employed to recruit participants. The researchers conducted in-depth, individual, open-ended interviews to collect data. Data were collected through semi-structured in-depth interviews with the participants. Qualitative data were examined using content analysis. A total of three main themes and seven subthemes were generated from the analysis. The analysis identified three main themes: emotional burden and coping with HPV, social loneliness and & imath;solation, and stigmatization and HPV. This study revealed that HPV-positive women experienced negative emotions such as anger and shame, faced social isolation, and encountered stigma from both their social environment and healthcare professionals. The findings highlight the need for psychosocial support and healthcare policies to improve the well-being of HPV-positive women.
Keywords: Human papilloma virus; sexually transmitted diseases; social isolation